An Alternative Method to Compute the Bit Error Probability of Modulation Schemes Subject to Nakagami-m Fading. (29th September 2010) - Queiroz Queiroz, Wamberto J. L. Wamberto J. L.; Lopes Lopes, Waslon T. A. Waslon T. A.; Madeiro Madeiro, Francisco Francisco; Alencar Alencar, Marcelo S. Marcelo S.
Abstract : This paper presents an alternative method for determining exact expressions for the bit error probability (BEP) of modulation schemes subject to Nakagami-m fading. In this method, the Nakagami-m fading channel is seen as an additive noise channel whose noise is modeled as the ratio between Gaussian and Nakagami-m random variables. The method consists of using the cumulative density function of the resulting noise to obtain closed-form expressions for the BEP of modulation schemes subject to Nakagami-m fading. In particular, the proposed method is used to obtain closed-form expressions for the BEP of M -ary quadrature amplitude modulation (M -QAM), M -ary pulse amplitude modulation (M -PAM), and rectangular quadrature amplitude modulation (I × J -QAM) under Nakagami-m fading. The main contribution of this paper is to show that this alternative method can be used to reduce the computational complexity for detecting signals in the presence of fading.